2018
DOI: 10.5468/ogs.2018.61.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment neutrophil-to-lymphocyte ratio and its dynamic change during neoadjuvant chemotherapy as poor prognostic factors in advanced ovarian cancer

Abstract: ObjectiveThe purpose of this study was to determine the prognostic implications of the pretreatment neutrophil-to-lymphocyte ratio (NLR) and its dynamic change during chemotherapy in patients with advanced epithelial ovarian cancer undergoing neoadjuvant chemotherapy.MethodsWe performed a retrospective analysis of 203 patients who underwent neoadjuvant chemotherapy prior to interval debulking surgery for advanced-stage ovarian cancer at Yonsei Cancer Hospital between 2007 and 2015. Pretreatment NLR was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
5
17
0
Order By: Relevance
“…Although a continuous high inflammatory status may contribute to the progression of sarcopenia, further research is needed about the most appropriate serum inflammatory markers relating skeletal muscle loss. As demonstrated in previous studies, 4,5,24 the inflammatory markers ALC and NLR recovered during NAC, and the high inflammatory status after NAC was associated not with OS but with poorer PFS. Changes in skeletal muscle may have a stronger prognostic value for long-term survival than do serum inflammatory markers.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although a continuous high inflammatory status may contribute to the progression of sarcopenia, further research is needed about the most appropriate serum inflammatory markers relating skeletal muscle loss. As demonstrated in previous studies, 4,5,24 the inflammatory markers ALC and NLR recovered during NAC, and the high inflammatory status after NAC was associated not with OS but with poorer PFS. Changes in skeletal muscle may have a stronger prognostic value for long-term survival than do serum inflammatory markers.…”
Section: Discussionsupporting
confidence: 76%
“…6 Recent studies have shown that serum inflammatory markers can be prognostic factors in EOC patients. 4,5,24 Aust et al reported that low mean muscle attenuation reflecting a state of cachexia is associated with serum levels of albumin and the cytokines eotaxin and IL-10. 18 However, the evidence linking serum inflammatory markers to skeletal muscle loss in advanced-stage EOC is still insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic power of SIR in relation to neoadjuvant therapies has been reported previously, involving rectal, ovarian, lung and breast cancers. A high mGPS was associated with poor response to NAC in rectal cancer (odds ratio (OR) 0·18, P = 0·006), and low NLR was associated with a good pathological response (OR 0·27, P = 0·046), although this did not retain independent significance in multivariable analysis.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, ovarian cancer patients with high level of NLR had poor response to chemotherapy [ 18 , 19 ]. Kim et al [ 20 ] suggested that dynamic changes in NLR during chemotherapy might help estimate a more accurate progression-free survival than pretreatment NLR. The positive correlation of pretreatment NLR with platinum resistance was demonstrated in our study as well.…”
Section: Discussionmentioning
confidence: 99%